BUDAYA KESELAMATAN PASIEN PADA PERAWAT DI INSTALASI PERAWATAN INTENSIVE RSUD ARIFIN ACHMAD PROVINSI RIAU - Yarnita, Yeni (Universitas Prima Indonesia, 2019)
Adverse events can be minimized the level of madness in the hospital by proclaiming behaviors that encourage the formation of patient safety known as the patient safety culture. Various health services, especially hospitals, data on Adverse events are still found annually. This study aims to determine the description of patient safety culture at nurses at the Intensive Care Installation Arifin Achmad Hospital of Riau. The population are all nurses in the Intensive Care Installation Arifin Achmad Hospital of Riau with size are 64 nurses with total sampling techniques in accordance with the inclusion and exclusion criteria. Data collection used a questionnaire adopted from Hospital Survey on Patient Safety (HSPSC) questionnaire published by The Agency For Healthcare Research and Quality (AHRQ). The results of the study prove that 56.3% of the patient's safety culture is negative category, and 43.8% of the patient's safety culture is positive category, importance to make programs that are related to patient safety culture are was need to improve the patient safety culture in Arifin Achmad Hospital of Riau